Benefits and harms of screening for and treatment of asymptomatic bacteriuria in pregnancy: a systematic review. Issue 1 (December 2016) - Angelescu, Konstanze; Nussbaumer-Streit, Barbara; Sieben, Wiebke; Scheibler, Fülöp; Gartlehner, Gerald
Abstract Background Most European and North American clinical practice guidelines recommend screening for asymptomatic bacteriuria (ASB) as a routine pregnancy test. Antibiotic treatment of ASB in pregnant women is supposed to reduce maternal upper urinary tract infections (upper UTIs) and preterm labour. However, most studies supporting the treatment of ASB were conducted in the 1950s to 1980s. Because of subsequent changes in treatment options for ASB and UTI, the applicability of findings from these studies has come into question. Our systematic review had three objectives: firstly, to assess the patient-relevant benefits and harms of screening for ASB versus no screening; secondly, to compare the benefits and harms of different screening strategies; and thirdly, in case no reliable evidence on the overarching screening question was identified, to determine the benefits and harms of treatment of ASB. Methods We systematically searched several bibliographic databases, trial registries, and other sources (up to 02/2016) for randomised controlled trials (RCTs) and prospective non-randomised trials. Two authors independently reviewed abstracts and full-text articles and assessed the risk of bias of the studies included. As meta-analyses were not possible, we summarised the results qualitatively. Results We did not identify any eligible studies that investigated the benefits and harms of screening for ASB versus no screening or that compared different screening strategies. We identified four RCTs comparing antibiotics with no treatment or placebo in 454 pregnant women with ASB. The results of 2 studies published in the 1960s showed a statistically significant reduction in rates of pyelonephritis (odds ratio [OR] = 0.21, 95 % confidence interval [CI] 0.07–0.59) and lower UTI (OR = 0.10, 95 % CI 0.03–0.35) in women treated with antibiotics. By contrast, event rates reported by a recent study were not statistically significantly different, neither regarding pyelonephritis (0 % vs. 2.2 %; OR = 0.37, CI 0.01–9.25, p  = 0.515) nor regarding lower UTI during pregnancy (10 % vs. 18 %; Peto odds ratio [POR] = 0.53, CI 0.16–1.79, p  = 0.357). Data were insufficient to determine the risk of harms. As three of the four studies were conducted several decades ago and have serious methodological shortcomings, the applicability of their findings to current health care settings is likely to be low. The recent high-quality RCT was stopped early due to a very low number of primary outcome events, a composite of preterm delivery and pyelonephritis. Therefore, the results did not show a benefit of treating ASB. Conclusions To date, no reliable evidence supports routine screening for ASB in pregnant women.